Delhi's Meatscapes: Cultural Politics of Meat in a Globalizing City. (January 2014) - Ahmad, Zarin
This article is located at the intersection of two distinct entry points—one, the development of Delhi as a global or world class city and two, the contested social location of meat in the city. Delhi is developing and is being projected as a world-class city with all the trappings of globalization which includes among other things state of art infrastructure, technologies, services and experiences. This development discourse is indeed a contested one and it is well-argued that urban transformations are beset with its own baggage of contradictions often resulting in marginalizing segments of its population. This article analyzes the construction of urban margins in contemporary globalizing Delhi through the lens of meat. Historical evidence shows that meat has been considered marginal to city spaces politically, spatially and socially. However, in the last two decades, the consumption, production, presentation and packaging of meat in India are in the throes of critical changes: in terms of technologies, geographies and actors. However, meat as a site is still beset with many tensions and contradictions which are located at the juncture between old and new forms of margin-making. Based on social and political contradictions regarding meat in India and specifically focusing on legal contestations and local activism around the relocation of the abattoir in Delhi, I argue that meat is a site around which margins are construed, transmitted and contested. Drawing from Appadurai, the article uses the concept of 'meatscapes' as a conceptual and linguistic tool to unravel the entangled reality of meat in Delhi.